9/11 in Nigeria: Translating Local into Global Conflicts - Harnischfeger, Johannes (AAeO - Afrikanistik-Aegyptologie-Online, 2012)
Many Nigerians saw 9/11 as part of a global confrontation between Muslims and Christians. As a religious event that involved worldwide communities, it could be replicated by actors in Nigeria. When news of the attacks in New York and Washington reached the citizens of Jos, Muslims and Christians engaged in a confrontation that may have claimed as many casualties as the 'original' events. According to the police, more than 3,000 lives were lost in the course of the riot and its suppression by police and army units. Yet news about the Jos catastrophe did not find their way into Western media. Let us take a closer look at this local conflict, exploring particularly in which ways the rival parties imagined it. Why did they identify with actors in North America and the Arab world? How did they appropriate the images of a global drama and make them reflect their own African realities? And how did these images reshape local antagonisms?